Gravity wave drag in a global circulation model of the Martian atmosphere: Parameterisation and validation - Collins, M; Lewis, SR; Read, P (1997)
The effect of orographically generated breaking gravity waves is parametrised in a global circulation model of the Martian atmosphere using schemes adapted from terrestrial models. The schemes are 'tuned' by comparing model integrations with and without gravity wave drag with temperatures derived from the Mariner 9 IRIS instrument. Without gravity wave drag the global circulation model temperature field has excessively cold upper level polar regions. Gravity wave drag can correct for such cold temperatures by warming the atmosphere adiabatically via a dynamically induced circulation. The model climatology is significantly improved in the polar regions with the introduction of the parametrisation. (C) 1997 COSPAR. Published by Elsevier Science Ltd.